Integration of Emotional Intelligence in the Strategic Services of Omah Tumbuh Potensi - Reni Dwi Wahyuni; Agoes Tinus Lis Indrianto; Hilda Yunita Wono (Journal of Practice Learning and Educational Development, 2026)
This study aims to understand how Emotional Intelligence (EI) is integrated in the strategic service process through the O.M.A.H© - Observe, Manage, Articulate/Act, Harvest framework at Omah Tumbuh Potensi (OTP). This study is motivated by the limited research that examines EI as part of the service process systematically, as most previous studies have focused more on the relationship between variables at the individual level. This research adopts a qualitative descriptive approach using in-depth interviews with purposively selected informants, including the CEO/Founder, Business Partner, Business Assistant, and 2 Clients. The data were analyzed using a thematic approach to identify patterns and meanings of EI integration in service processes. The results of the study show that EI not only functions as an individual competency in the OTP team, but also as an emotional capability that is operationalized through a structured service process. The O.M.A.H© framework serves as an applied model that allows the integration of EI in strategic services to be consistent. The findings of the study also show that superior service in the context of OTP is interpreted as a relational outcome formed through the quality of interaction and client experience during the service process. This research makes a theoretical contribution by expanding the understanding of EI as part of the service process and introducing the O.M.A.H© framework in strategic service design. Practically, this research also provides implications for service organizations in developing an EI-based service approach that is integrated in strategic services on a sustainable basis.